Postawy nauczycielek i nauczycieli wobec kształcenia na odległość w czasie pandemii COVID-19 - Jaskulska , Sylwia; Jankowiak , Barbara (Studia Edukacyjne, 2020)
Despite the explosion of studies on social consequences of the COVID-19 outbreak, still little is known about the situation of teachers. This research report presents results of a study on teacher’s attitudes toward distance education during the COVID-19 pandemic and their associations with selected characteristics related to the teacher’s profession. The study consisted in answering questions in an online survey. Nearly eight hundred correctly completed surveys were collected. Multivariate analysis of variance (MANOVA) was applied to compare differences between the variables. The results show that the lowest averages on a Likert-type scale describe the cognitive component of attitudes, and the highest ones describe the behavioral component. Awareness of problems with the implementation of the curriculum and basic tasks of the school in the form of a distance education result in teachers’ competence increase and taking specific action. Gender and seniority are not associated with the teachers’ attitudes toward distance education. The type of school and the level of education were associated with attitudes towards distance education. Special schools teachers had the worst experience with distance education. The possible implications of these outcomes are discussed.